Effect of Ca doping on the arbitrary canting of magnetic exchange interactions in La1-xCaxMnO3 nanoparticles - Ali, Akhtar; Shah, Wiqar H.; Safeen, Akif; Ali, Liaqat; Tufail, Muhammad; Ullah, Zakir; Safeen, Kashif; Eldin, Sayed M.; R. Ali, Mohamed; Sohail, Muhammad; Imran, Naveed (Frontiers in Materials, 2023)
La1-xCaxMnO3 nanoparticles (x=0.1, 0.2, 0.3) (LCMO NPs) were synthesized through the co-precipitation method. The prepared samples were investigated by using X-ray diffraction (XRD), which confirmed the single-phase structure. The nanoparticle’s crystallite size has been confirmed by using Debye-Scherrer's formula. Scanning electron microscopy (SEM) showed that the size of nanoparticles was between 33-55 nm. Energy-dispersive X-ray spectroscopy (EDX) has been used to determine the elemental composition of samples. The four-probe method was used to measure the temperature-dependent electrical resistivity. The magnetic properties like hysteresis loop, magnetoresistance, and magnetization versus temperature were measured using a vibrating sample magnetometer (VSM). The study of magnetization vs. applied magnetic field M(H) showed that at 77 K, all the loops displayed the behavior of ferromagnetism. DC Magnetization vs. temperature at 70 Oe applied field for all the samples showed a paramagnetic-ferromagnetic phase transition. The decrease in Curie temperature Tc by increasing concentration of x has been observed. The real and imaginary parts of temperature-dependent ac magnetic susceptibility have been measured, which shows the transition from ferromagnetic to paramagnetic phase at a particular temperature Tc which has DC magnetization behavior.